IMPACT OF LOW VERSUS HIGH VACUUM SUCTION DRAINAGE ON DURATION OF HOSPITAL STAY AFTER MODIFIED RADICAL MASTECTOMY: Vacuum Suction Drainage After Radical Mastectomy - Mansoor, Junaid; Ahmed, Maqbool; Junaid, Zartash; Umair, Muhammad; Meshwani, Ahmad Hussain (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the efficacy of low pressure vs high vacuum suction drains after modified radical mastectomy in terms of earlier removal and its impact on duration of hospital stay. Study Design: A randomized clinical trial. Place and Duration of Study: The study was conducted at Military Hospital Rawalpindi and CMH Peshawar over a period of 12 months from March 2010 to March 2011. Patients and Methods: Sixty trucut/biopsy proven, early invasive breast cancer patients undergoing modified radical mastectomy were randomized into groups A (n=30) and B (n=30) to receive high vacuum (400 mm Hg) suction drains or low vacuum suction drains (200 mm Hg) at completion of operation. Drains were recharged to the specified pressure daily and drain output was recorded. Drains were removed when the daily drainage reduced to 30 ml. Results: 28 patients in group A & 27 patients in group B were finally included in the study. Mean hospital stay in low vacuum suction group was 4.96 ± 0.898 days which was 32.9% shorter than 7.39 ± 1.397 days for high pressure suction group (p< 0.005). Conclusion: The use of low vacuum vs high vacuum drains after modified radical mastectomy reduces the hospital stay significantly.